Quality of Student Literature Critical Essay Writing In the Mimetic Perspective - Septyanti, Elvrin; Zulhafizh, Zulhafizh (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine the skills and quality of writing literary criticism essays of Study Program students of Indonesian Language and Literature education based on a mimetic approach. The method used is a qualitative method. The techniques used in this study are: (1) literature review, (2) observation, (3) documentation techniques, and (4) analytical techniques. The research data was obtained based on the students writing sheet about the literary criticism essay of the novel "MemangJodoh" by MarahRusli. Analysis sheet based on the assessment scale of literary criticism essay quality with checklist as an instrument. This research instrument was arranged based on (1) content (ideas expressed), (2) content organization, (3) grammar, (4) style: choice of structure and wealth of words, (5) spelling, (6) linking work with reality , (7) linking works with writers, (8) linking works with readers, (9) involving scientific disciplines. Furthermore, student writing is read and assessed based on the predetermined rubric. The results of the study showed that overall the ability and quality of writing in the students literary essay critics were found to be of medium standard with a mean of 2.06.